POLA TANAM OPTIMAL PADA LAHAN PANTAI DI KABUPATEN KULONPROGO - Letari Rahayu Waluyati (Agro Ekonomi, 2001)
The objective of this study is to observe the optimal crops pattern of coastal land in Kulon Progo district. Selection of the location is used purposive method at six villages within four sub-district which have coastal land such as Temon, Wates, Panjatan and Galur. Sixty farmers sampling were taken as purposive method for several plant pattern of coastal land.The result showed that most commodities are horticulture such as chili, watermelon and peanut. The general problem for planting in the coastal land are water and sea wind. They use water well pump and "renteng" well , while for wind barrier they use coconut leaves and acacia.The crops pattern of the farmer who cultivate in coastal land 0,5 - 2 ha/year and no credits, crops pattern optimal are (1) peanut - chili-watermelon; (2) watermelon- ch/i-chili and (3) "bero" - chili-watermelon. For the same land, for farmer who have KUT credits with discount rate 10,5%, crops pattern optimal are (1) peanut-chili-watermelon (2) watermelon-chili-chili. The same crops pattern optimal suggested for credit with discount rate 22%